Quality assessment of traditional and conventional medicine clinical practice guidelines for osteoporosis. Issue 5 (5th February 2021) - Kim, Jung-Hyun; Seo, Byung-Kwan; Baek, Yong-Hyeon
Abstract : Abstract: Numerous studies have reported the variable quality of clinical practice guidelines (CPGs) across various domains. The aim of this study was to systematically assess the quality, methodology, and consistency of recently developed traditional and conventional medicine CPGs that focus on the management of osteoporosis and provide helpful recommendations for patients with osteoporosis. From June 2020 to July 2020, CPGs with osteoporosis targeting any age were systematically retrieved. All CPGs of traditional and conventional medicine related to the assessment and diagnosis, management, and clinical therapeutic and pharmacological recommendations with osteoporosis were eligible for inclusion in this study. The excluded documents included guidelines without recommendations, secondary publications derived from CPGs, consensus statements, or consensus conferences based on the opinion of panelists, systematic reviews, editorials, clinical trials, and single-author documents. The quality of CPGs was independently examined by three assessors using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument. AGREE II consists of 6 domains; scope and purpose, stakeholder involvement, rigor of development, clarity of presentation, applicability, and editorial independence. Consequently, selected CPGs were graded as recommended (A), recommended with modifications (B), or not recommended (C), and the specific treatments and preventive recommendations in the CPGs were summarized. The quality of the 15 CPGs assessed varied across the AGREE II domains. The overall quality ranged from 3.0 to 6.0 out of 7. The domain that had the highest scores were "clarity of presentation, " with a mean value of 69.0% (range 46%–83%); "editorial independence" had the lowest score of 30.2% (range 0%–75%). The conventional CPGs focused on pharmacological treatments, calcium and vitamin D intake, and prevention, while the traditional CPGs consistently emphasized on herbal medicine and non-pharmaceutical treatment and management. Further development of CPGs will require improvement in domains where low item scores have been obtained in the quality assessment in this present study. Further research is needed on alternative modalities for osteoporosis, especially complementary approaches, and higher quality CPGs are needed to facilitate evidence-based clinical practice.